Aging rheological characteristics of SBR modified asphalt with multi-dimensional nanomaterials. (1st October 2017) - Zhu, Chongzheng; Zhang, Henglong; Xu, Guoqing; Shi, Caijun
Highlights: The rheological properties of SBRMA with nanomaterials are studied. The aging resistance of SBRMA can be improved by multi-dimensional nanomaterials. The recommended proportion of multi-dimensional nanomaterials is confirmed as 1%OEVMT + 3%nano-ZnO. Abstract: The purpose of this work is to research the influence of multi-dimensional nanomaterials composed of surface modified nano-zinc oxide (nano-ZnO) and organic expanded vermiculite (OEVMT) on rheological characteristics of styrene butadiene rubber modified asphalt (SBRMA) before and after different aging methods. The styrene butadiene rubber modified asphalts (SBRMAs) with various proportions multi-dimensional nanomaterials were produced by melt blending method. All binders were aged by rolling thin film oven test (RTFOT), pressure aging vessel (PAV) and ultraviolet (UV) aging. Dynamic shear rheometer (DSR) was utilized to test the rheological properties of all samples, as well as the performance grade (PG) of all binders was checked. The results show that the addition of multi-dimensional nanomaterials can enhance the shear deformation resistance and elastic behavior of SBRMA. Based on the RTFOT, PAV and UV aging test results, both thermal oxidative and photo oxidative aging resistance of SBRMA can be improved significantly by introducing multi-dimensional nanomaterials. Moreover, the optimal proportion of multi-dimensional nanomaterials in SBRMA is confirmed as 1%OEVMT + 3%nano-ZnO. Besides, the PG test result verifies that the PG of SBRMA after 1%OEVMT + 3%nano-ZnO modifying maintains unchanged.